Novel flavagline‐like compounds with potent Fli‐1 inhibitory activity suppress diverse types of leukemia. (20th November 2018) - Song, Jialei; Yuan, Chunmao; Yang, Jue; Liu, Tangjingjun; Yao, Yao; Xiao, Xiao; Gajendran, Babu; Xu, Dahai; Li, You‐Jun; Wang, Chunlin; Liu, Wuling; Wen, Min; et al.
Abstract : E26 transformation‐specific (ETS) gene family contains a common DNA‐binding domain, the ETS domain, responsible for sequence‐specific DNA recognition on target promoters. The Fli‐1 oncogene, a member of ETS gene family, plays a critical role in hematopoiesis and is overexpressed in diverse hematological malignancies. This ETS transcription factor regulates genes controlling several hallmarks of cancer and thus represents an excellent target for cancer therapy. By screening compounds isolated from the medicinal plant Dysoxylum binectariferum in China, we identified two chemically related flavagline‐like compounds including 4′‐demethoxy‐3′, 4′‐methylenedioxyrocaglaol and rocaglaol that strongly inhibited Fli‐1 transactivation ability. These compounds altered expression of Fli‐1 target genes including GATA1, EKLF, SHIP1, and BCL2. Consequently, the flavagline‐like compounds suppressed proliferation, induced apoptosis, and promoted erythroid differentiation of leukemic cells in culture. These compounds also suppressed erythroleukemogenesis in vivo in a Fli‐1‐driven mouse model. Mechanistically, the compounds blocked c‐Raf‐MEK‐MAPK/ERK signaling, reduced phosphorylation of eukaryotic translation initiation factor 4E (eIF4E), and inhibited Fli‐1 protein synthesis. Consistent with its high expression in myelomas, B‐cell lymphoma, and B chronic lymphocytic leukemia (B‐CLL), pharmacological inhibition of Fli‐1 by the flavagline‐like compounds or genetic knock‐down via shRNA significantly hindered proliferation of corresponding cell lines and patients' samples. These results uncover a critical role of Fli‐1 in growth and survival of various hematological malignancies and point to flavagline‐like agents as lead compounds for the development of anti‐Fli‐1 drugs to treat leukemias/lymphomas overexpressing Fli‐1. Abstract : The Fli‐1 oncogene drives various cancers and its genetic ablation suppresses growth. Using a screening assay, we identified flavagline‐like compounds that inhibited Fli‐1, leading to suppression of leukemia in vitro and in vivo . We discovered that these compounds reduced Fli‐1 protein synthesis by blocking c‐Raf‐MEK‐MAPK/ERK signaling and additionally inhibited eIF4E phosphorylation. These agents offer lead compounds for anti‐Fli‐1 drug development.